The Effect Of Total Asset Turnover And Debt To Asset Ratio On Return On Asset At PT. Mandom Indonesia Tbk 2015-2024 Period - Saputra, Gunawan; Nurcahayati, Siti (Doktoral Ilmu Manajemen, Universitas Pasundan, 2025)
This study aims to analyze the effect of Total Asset Turnover and Debt to Asset Ratio both partially and simultaneously on Return on Assets at PT Mandom Indonesia Tbk for the period 2015-2024. This research method uses a quantitative method. The sample of this study is financial statement data in the form of balance sheets and profit and loss at PT Mandom Indonesia Tbk for the period 2015 to 2024. Data analysis used includes classical assumption tests, multiple linear regression tests, coefficient of determination tests, partial tests and simultaneous tests. The results of this study based on the classical assumption test did not find any variables that deviate from the classical assumptions. These results indicate that the available data has met the requirements for using a multiple regression equation model. The results of the t test show that partially Total Asset Turnover has a positive and significant effect on Return on Assets, this is evidenced by the results of t count greater than t table (3.087 > 2.365) and the level of significance (0.015 < 0.05). Debt to Asset Ratio has a negative and significant effect on Return on Assets, this is evidenced by the calculated t result being greater than the t table (2.672 > 2.365) and its significance level (0.028 < 0.05). And simultaneously, Total Asset Turnover and Debt to Asset Ratio have a significant effect on Return on Assets, this is evidenced by the calculated F result being greater than the F table (6.012 > 4.74) and its significance level (0.030 < 0.005), with a contribution of 52.7%, while the remaining 47.3% is influenced by other factors.